Trout fishing on an estuary of Lake Eucumbene in Snowy Mountains, in late 1960's - Carter, Jeff, 1928-2010. (Between 1960 and 1970., 1960)
"The angler is Percy Carter (father of Jeff Carter), with a nice catch of fish. Rainbow and brown trout fingerlings, bred at Jindabyne hatchery, were periodically released into district waters until it was realised the area was overstocked, particularly with older, cannibal fish that thrived on the young fingerlings. As a result, the traditional closed seasons against fishing were abandoned, in the hope more mature fish would be removed, thus aiding the survival of younger fish. People magazine 5 February 1957, page 4-8; 9 November 1960, page 13-15."--Description supplied by photographer.
Title from caption list supplied by photographer, see file NLA/13141.
Condition: Good.
Also available online
Purchased from the photographer, 2005.
Keywords: Carter, Percy -- Photographs; Fishing -- New South Wales -- Lake Eucumbene Region -- Photographs